Evaluating the reach, effectiveness, adoption, implementation and maintenance of the Resistance Training for Teens program - Sarah G. Kennedy; Jordan J. Smith; Paul A. Estabrooks; Nicole Nathan; Mike Noetel; Philip J. Morgan; Jo Salmon; Gessika C. Dos Santos; David R. Lubans (BMC, 2021)
Abstract Background Physical activity guidelines recommend young people engage in regular muscle-strengthening activities (e.g., resistance training [RT]). However, few school-based physical activity interventions have been delivered at-scale or promoted RT. The aim of this study was to evaluate the reach, effectiveness, adoption, implementation and maintenance of the Resistance Training for Teens (RT for Teens) program. Methods Data were collected between August 2015 and October 2020. RE-AIM was operationalized as: (i) Reach: number and characteristics of students estimated to be exposed to the program; (ii) Effectiveness: impact of the program on student-level outcomes measured in a subsample of 750 students from 17 schools; (iii) Adoption: number and representativeness of schools with one or more teachers trained to deliver the program; (iv) Implementation: extent to which the program was delivered as intended; and (v) Maintenance: extent to which the program was sustained in schools. Results The estimated program reach was ~ 10,000 students, out of a total student population of ~ 200,000 (~ 5%). Students were from diverse socioeconomic and ethnic backgrounds. Improvements in muscular fitness, RT self-efficacy, perceived cardiorespiratory fitness and flexibility, and participation in muscle-strengthening physical activities were documented. A total of 30 workshops were delivered, involving 468 teachers from 249 schools from diverse geographical regions. Implementation varied considerably, with teachers adapting the program to suit the context of their school and student cohorts. However, RT skill development and the promotion of muscular fitness were the session components delivered most during sessions. Teachers' adherence to the SAAFE (Supportive, Active, Autonomous, Fair and Enjoyable) teaching principles was high. Approximately 30% of teachers (144/476) registered to use the RT for Teens app. At the school-level, 37% (93/249) of schools had at least one registered user (teacher and/or student). A total of 2,336 workouts and 3,116 fitness tests were completed by registered users. Of the 249 schools represented, 51 (20.5%) sent an additional (previously untrained) teacher to a second workshop. Conclusions The RT for Teens program had broad reach and adoption. However, intervention delivery varied considerably across schools and additional support strategies are required to optimize intervention implementation and maintain program delivery over time. Future studies will benefit from the utilization of accepted frameworks, recommendations and guidelines for implementation research. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12621000352808), retrospectively registered 1st February 2021.